Computational Fluid Dynamics Analysis of Penstock Branching in Hydropower Project - Kandel, Bipin; Luitel, Mahesh Chandra (Journal of Advanced College of Engineering and Management, 2019)
The penstock branching manifold is regarded as most critical part of the hydropower project. A computational research has been carried out to conclude the most efficient branching manifold with has more than or equal to three units of turbine. Starting from the base data from a project "Solukhola-Dudhkoshi Hydropower Project, 86 MW" for three units of turbines. More than 20 models were prepared to visualize flow pattern, to minimize the head loss and mas flow variation among 3 different units. The research has been finally concluded to go towards a single trifurcation instead of successive two bifurcation or individual branching form main branches.